Digitalization, AI, and Service Quality in Islamic Banks: Customer Satisfaction and Knowledge as Parallel Mediators of Customer-Perceived Financial Performance - Rahayu, Sri; Tullah, Dewi Sarifah; Suginam, Suginam; Nur, Sobihatun (Institut Bisnis dan Informatika Kesatuan, 2025)
Digitalization and artificial intelligence (AI) are reshaping retail banking, yet evidence on how they translate into financial performance in Islamic banks—particularly through customer-level mechanisms—remains limited. This study investigates the effects of digitalization, AI, and service quality on customer-perceived financial performance, with customer satisfaction and customer knowledge as parallel mediators. A cross-sectional survey was administered to 120 customers of Islamic banks in Medan, Indonesia, selected via purposive sampling (active users of digital services who interacted with AI features within the last six months). Data were analyzed using SEM–PLS. The measurement model met standard quality criteria (convergent and discriminant validity; reliability), and the structural model showed good fit (SRMR = 0.07) and predictive relevance (Q² > 0). The model explained substantial variance (R²: satisfaction = 0.431, knowledge = 0.441, perceived financial performance = 0.760). Digitalization, AI, and service quality positively affected satisfaction and knowledge, which in turn improved customers’ perceived financial performance; both mediators exhibited significant indirect effects. These findings indicate that robust digital channels and AI capabilities, when delivered with consistent service quality and coupled with effective customer education, enhance satisfaction and knowledge—key pathways through which customers perceive stronger financial performance of their Islamic bank. Practical implications and avenues for future research are discussed. Keywords: Digitalization; Artificial Intelligence; Service Quality; Customer Satisfaction; Customer Knowledge; Customer-Perceived Financial Performance; Islamic Banks.